Collaborative inquiry integrated technological pedagogical content knowledge to improve higher-order thinking skills - Nur Lailatin Nisfah; Endang Purwaningsih; Parno Parno (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran)
This study aimed to generate a teaching package in a lesson plan and student worksheet using the TPACK integrated Collaborative Inquiry model, which can improve higher-order thinking skills (HOTS) validly and effectively. The development research design followed the four-D-models development model, consisting of 4 phases: define, design, develop, and disseminate. At define, several observations and literacy studies were carried out. At design, teaching materials were designed. The experts validated the teaching materials in development, namely two lecturers and two teachers as users. Based on the validation results, it is found that the lesson plan and student worksheet were within the good or valid criteria to be used. HOTS was measured using two-tier multiple-choice in the form of 15 questions with good categories and high-reliability categories. The feasibility test was based on expert validation. The results show that the teaching material is in good criteria, so it is suitable for use under several conditions. The implementation results can affect the differences in the results of the pretest and post-test student’s HOTS-based observation during learning and increased scores.